1993
DOI: 10.1093/ajcn/58.2.215
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between iron deficiency and anemia in Venezuelan children

Abstract: The iron status of 3228 subjects from the nutrition survey Proyecto Venezuela was studied. The sample included children from 1 to 16 y of age grouped by age and sex. Values for three indicators of iron status were compared: hemoglobin concentration, serum ferritin concentration, and percentage saturation of serum transferrin. In all groups there was a strong overlap in the hemoglobin concentration distribution curves for non-iron-deficient and iron-deficient subjects classified as such according to the other t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 15 publications
0
13
0
1
Order By: Relevance
“…In the last stage, although hemoglobin determination by itself is not the best indicator to define iron deficiency, it is the easiest test used to screen for a significant iron deficiency (Cook, 1999). Several studies have shown that iron deficiency is the main cause for a low hemoglobin concentration (Taylor et al, 1993;Palupi et al, 1997;García-Casal et al, 1998;Nestel et al, 1999). Therefore, for this study hemoglobin concentration was measured as an IDA indicator.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last stage, although hemoglobin determination by itself is not the best indicator to define iron deficiency, it is the easiest test used to screen for a significant iron deficiency (Cook, 1999). Several studies have shown that iron deficiency is the main cause for a low hemoglobin concentration (Taylor et al, 1993;Palupi et al, 1997;García-Casal et al, 1998;Nestel et al, 1999). Therefore, for this study hemoglobin concentration was measured as an IDA indicator.…”
Section: Discussionmentioning
confidence: 99%
“…Growth retardation has been related to anemic condition and also to VAD (Mwanri et al, 2000) although some studies have questioned the effect of these micronutrients on child growth (Bhandari et al, 2001;Rahman et al, 2002). In Venezuela, few national and sub-national individual studies on IDA and VAD have been reported (Taylor et al, 1993;Solano et al, 1996;Castejó n et al, 2001;Amaya-Castellano et al, 2002;Paéz Valery et al, 2002). However, no attempts have been made to determine the coexistence of both micronutrient deficiencies and growth deficiency in the same children population.…”
Section: Introductionmentioning
confidence: 99%
“…1,13,20 A maior vulnerabilidade desse grupo etário poderia ser atribuída às seqüelas do desmame precoce, à monotonia alimentar, à introdução de leite fluido, ocasionando micro-hemorragias no trato gastrointestinal, bem como maior predisposição às doenças infecciosas 14 e parasitárias. 16 A tendência observada no comportamento das concentrações de hemoglobina, com elevação significativa de seus níveis médios com o aumento da idade após os 36 meses, seria um elemento a ser considerado na priorização de determinados grupos biológicos, no que diz respeito à adoção de medidas emergenciais em situações onde os recursos humanos, materiais e financeiros são escassos e/ou limitados.…”
Section: Discussionunclassified
“…In a study between the relationship between iron de ficiency and anemia in Venezuelan children, Taylor et al (31) using the following criteria: hemoglobin con centrations below 11.5g/dL, serum ferritin concentra tion below 10ng/mL, and transferrin saturation below 14%, for children 4-7 years old, showed a certain pro portion of the children with apparently normal hemo globin concentrations were iron deficient. Although the effects of milder iron deficiency without anemia are not clear, cellular immunity may be affected by iron defi ciency before the overt symptoms of anemia appear (28 …”
Section: Discussionmentioning
confidence: 99%